2009
DOI: 10.2478/s11536-009-0026-5
|View full text |Cite
|
Sign up to set email alerts
|

The concentration of uric acid in patients with metabolic syndrome and cardiovascular diseases

Abstract: AbstractThe association of elevated serum uric acid (hyperuricemia, gout) with the presence of classical coronary risk factors and coronary artery disease (CAD) or myocardial infarction (MI) has been analysed in many epidemiological studies. Numerous studies have revealed that hypertension, high body mass index (BMI), lipid disorders (especially raised triglyceride (TG) levels and low high dense lipoprotein cholesterol (HDL-C) level), and increased creatinine or insulin levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“…Взаимосвязь между ГУ, подагрой и компонентами МС, включая нарушения углеводного обмена, показана во многих, в том числе популяционных, исследованиях [18][19][20]. Накапливаются данные о том, что наличие подагры повышает риск развития МС и непосредственно СД2.…”
Section: Discussionunclassified
“…Взаимосвязь между ГУ, подагрой и компонентами МС, включая нарушения углеводного обмена, показана во многих, в том числе популяционных, исследованиях [18][19][20]. Накапливаются данные о том, что наличие подагры повышает риск развития МС и непосредственно СД2.…”
Section: Discussionunclassified
“…Many studies have shown a relationship between hyperuricemia and cardiovascular disease (Kostka-Jeziorny et al, 2019;Kowalski et al, 2009;Zhang et al, 2019). Several studies on hyperuricemia patients have reported SUA concentration as a marker of pathophysiology processes that correlated with the development of cardiovascular disease (Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%